Mindful practice and narrative medicine to educate undergraduate medical professionalism. - Jofré Pavez, Pamela; Flores Benner, Pía; Oyanedel , Rebecca; Valenzuela Pepe, Rodrigo; Gigoux Lopez, Juan Pablo; Vergara Fisher , Rodrigo (Spanish Journal of Medical Education, 2024)
Medical professionalism and clinical bioethics are sought-after competencies in the medical degree at Valparaíso University and teaching them is a challenging. Narrative medicine as a pedagogical tool addresses issues associated with these two competencies, generating significant learning, while “mindful practice” refers to the systematic use of contemplative methodologies. This article aims to show an innovative educational experience in medical professionalism that contemplates mindful practice or full attention in clinical and narrative medicine. During 2022 a practical-reflective workshop on professionalism was implemented, in the fifth year in the subjects of Adults Clinics, Pediatrics and Women' Health. Sessions included mindfulness practices and exposure to art (movies, poetic reflection, literature, comics, museum immersion), as well as reflective writing. The course was divided into three sections, each participated in 6 sessions of 3 hours. The topics were selected by previous surveys of teachers and students. Each sessions included a survey to evaluate the experience and perception of the students, 98 students participated, and the analysis of reflective texts, stories and poems submitted voluntarily plus feedback survey, indicated high acceptance of the activity, positive assessment of mindfulness experiences applicable to the clinic, learning environment and perception of well-being. Educating professionalism by generating spaces for reflection through a narrative medicine workshop and mindfulness practices is feasible and positively valued by medical students. exposure to art (movies, poetic reflection, literature, comics, museum immersion), as well as reflective writing. The course was divided into three sections, each participated in 6 sessions of 3 hours. The topics were selected by previous surveys of teachers and students. Each sessions included a survey to evaluate the experience and perception of the students, 98 students participated, and the analysis of reflective texts, stories and poems submitted voluntarily plus feedback survey, indicated high acceptance of the activity, positive assessment of mindfulness experiences applicable to the clinic, learning environment and perception of well-being. Educating professionalism by generating spaces for reflection through a narrative medicine workshop and mindfulness practices is feasible and positively valued by medical students.